Health expenditure and Environmental pollution in Latin American and Caribbean’s - Takyi Kwabena Nsiah; Ruth A Danso; Ofori Charles; Mmieh K. Raphael (Garuda Prestasi Nusantara Consulting, 2022)
This analysis explores the connections between economic growth (GDP), environmental degradation (CO2), population growth (PG), and health spending (HE) using a pooled mean group calculation (ARDL-PMG) autoregressive distributed lag model and employing Granger causality checks to Latin American and Caribbean States for the period from 1996 to 2017. Short-term causalities from CO2 to HE is unidirectional and permanent. Over the short term, the causal path between CO2 and GDP is unobservable. Furthermore, unidirectional short-run causality from GDP to HE was suggested in the article analysis. There are short-run bidirectional causalities between GDP, CO2, and HE when measured per two or more independent variables. If we apply CO2 to the GDP and PG factors, the causality of HE is measurable, and the GDP and PG pair's causality to health spending is neutral. Similarly, if we apply population growth to the health expenditures and gross domestic product of the variable, there is causality. Long-run bidirectional causalities occur between GDP, CO2, and HE. For the research outcomes, the causality from HE to GDP is not strong. The clear causality of health spending and CO2 to economic development is neutral if we measure each pair of variables. The long-term PMG projections indicate that environmental pollution is increased by population growth and health spending, while economic growth lowers environmental pollution.